Model Kurikulum Bahasa Arab Kelas X Studi Komparatif Kurikulum 2013 dan Kurikulum Ismuba - Muhammad Ilfan Fauzi Ilfan (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2019)
Abstract This paper discusses the Arabic learning curriculum that has similar patterns of development in the 2013 curriculum and the Ismuba curriculum. The purpose of this paper is to find out the differences and similarities in the implementation of the 2013 curriculum and the Ismuba curriculum in the tenth grade Arabic learning. The basic principle of the present study is the similarity of levels and curriculum development systems that are line staff or top down. An in-depth study is needed to see how the design of the tenth grade Arabic curriculum process has been applied by the Indonesian Ministry of Education and Culture and the Muhammadiyah Basic Education Council. Library research method is used with content analysis in the form of descriptive analysis and comparative analysis. The results of the analysis in this paper found that there are similarities in the application of Core Competencies (KI) of Arabic subjects that are specifically Islamic and there are differences in the development of Basic Competencies (KD) as well as the strengths and weaknesses of each Arabic curriculum design system development in the tenth grade from the Ministry of Education and Culture of the Republic of Indonesia and the Muhammadiyah Basic Education Council. Furthermore, there are striking differences on the material. Ismuba has eight topics by prioritizing qowaid and mufradat elements and does not separate the four language skills while the 2013 curriculum has six topics of discussion and emphasizes on exercises (tadrib) on separate discussion of four language skills. Keywords: 2013 Curriculum, Ismuba Curriculum, Arabic Abstrak Tulisan ini mendiskusikan tentang kurikulum pembelajaran bahasa Arab yang mempunyai kemiripan pola dan corak pengembangan pada kurikulum 2013 dan kurikulum Ismuba. Tujuan tulisan ini untuk mengetahui bagaimana perbedaan dan persamaan implementasi kurikulum 2013 dan kurikulum Ismuba pada pembelajaran bahasa Arab kelas X. Pokok dasar kajian dalam tulisan ini yaitu adanya kesamaan jenjang dan sistem pengembangan kurikulum yang bersifat line staff atau top down sehingga perlu dikaji lebih mendalam bagaimana rancangan proses kurikulum bahasa Arab kelas X yang telah diterapkan oleh Kemendikbud RI dan Majelis Dikdasmen Muhammadiyah. Jenis penelitian yang digunakan penelitian pustaka dengan konten isi (analysis content) berupa analisis deskriptif dan analisis komparatif. Hasil analisis dalam tulisan ini ditemukan bahwa terdapat persamaan dalam penerapan Kompetensi Inti (KI) mata pelajaran bahasa Arab yang berciri khas keislaman dan terdapat perbedaan dalam pengembangan Kompetensi Dasar (KD) serta kelebihan dan kekurangan dari masing-masing rancangan sistem pengembangan kurikulum bahasa Arab kelas X dari Kemendikbud RI dan Majelis Dikdasmen Muhammadiyah. Lebih lanjut, Perbedaan mencolok terdapat pada sisi materi bahwa Ismuba mengusung delapan topik dengan mengedepankan unsur-unsur qowaid dan mufradat serta tidak memisahkan empat ketrampilan bahasa sedangkan pada kurikulum 2013 mengusung enam topik pembahasan dan lebih mengedepankan latihan (tadrib) pada pembahasan yang terpisah dari empat ketrampilan berbahasa. Kata kunci: Kurikulum 2013, Kurikulum Ismuba, Bahasa Arab